2003
DOI: 10.1074/jbc.m303552200
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylation Regulates the Stability of Trypanosoma brucei Mitochondrial RNAs

Abstract: Polyadenylation of RNAs plays a critical role in modulating rates of RNA turnover and ultimately in controlling gene expression in all systems examined to date. In mitochondria, the precise mechanisms by which RNAs are degraded, including the role of polyadenylation, are not well understood. Our previous in organello pulsechase experiments suggest that poly(A) tails stimulate degradation of mRNAs in the mitochondria of the protozoan parasite Trypanosoma brucei (Militello, K. T., and Read, L. K. (2000) Mol. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 39 publications
4
54
1
Order By: Relevance
“…In in vitro decay assays, replacement of four adenosine residues within a 20 nt 3′ tail with a stretch of four uridines did not affect the ability of the 3′ tail to stabilize edited RNA (20). However, the same replacement partially impeded the rapid decay of polyadenylated unedited RNA (19).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In in vitro decay assays, replacement of four adenosine residues within a 20 nt 3′ tail with a stretch of four uridines did not affect the ability of the 3′ tail to stabilize edited RNA (20). However, the same replacement partially impeded the rapid decay of polyadenylated unedited RNA (19).…”
Section: Introductionmentioning
confidence: 94%
“…We previously showed that poly(A) tails regulate stability of mitochondrial transcripts in T. brucei (19,20,48). Thus, we wanted to directly determine whether kPAP2 plays a role in regulating RNA abundance in T. brucei mitochondria.…”
Section: Analysis Of Mitochondrial Rna Abundance and Long 3′ Tail Synmentioning
confidence: 99%
See 1 more Smart Citation
“…In trypanosome mitochondria, the length of the poly(A) tail is dependent on the edited status of the mRNA (15)(16)(17). The role of long poly(A) is unknown, whereas short poly(A) seems to stimulate mRNA degradation (18).…”
Section: Mammalian Mitochondrial (Mt) Mrnas Have Short Poly(a) Tails mentioning
confidence: 99%
“…These include the processing of polycistronic transcripts by 39 and 59 cleavage, transcript maturation through polyadenylation and RNA editing, and RNA turnover (Bhat et al 1992;Militello and Read 1999;Madison-Antenucci et al 2002;Stuart and Panigrahi 2002;Simpson et al 2003;Kao and Read 2005;Lukes et al 2005). These events are controlled by strict regulatory mechanisms for which there are presumably many cis-and trans-acting factors that act to modulate transcript utilization and abundance (Ryan et al 2003;Kao and Read 2005). RNA-binding proteins play a pivotal role in all aspects of cellular RNA processing and utilization (Dreyfuss et al 2002), and several RNA-binding proteins have been described in T. brucei mitochondria, including TBRGG1 (Vanhamme et al 1998), REAP-1 (Madison-Antenucci and Hajduk 2001), RBP16 (Pelletier and Read 2003), and MRP1/2 (Vondruskova et al 2005).…”
Section: Introductionmentioning
confidence: 99%